Effect of metadiscourse on reading comprehension of Iranian EFL learners - Zahra Zarrati,; Radha M.K Nambiar,; Tengku Nor Rizan Tg Mohd Maasum, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2014)
Metadiscourse, known as discourse about ongoing discourse, has been the subject of discourse research from a wide range of perspectives. In academic contexts, knowledge of metadiscourse as a prominent feature of all types of academic discourse provides second language readers with information about writer’s attitudes towards the text and the readers. Over the past decade there has been a growing interest in conducting studies investigating different aspects of metadiscourse in relation to language learning. The present study hopes to contribute to the study of metadiscourse by investigating its effect on EFL learners’ reading comprehension (with three levels of reading proficiency: low, medium, and high) when faced two text types –academic and general. To this end, data were collected through two instruments, namely a TOEFL reading comprehension sample test and a reading comprehension test which consisted of two text types was developed for the purpose of this study. Two versions of this reading comprehension test were developed: one with metadiscourse enriched texts and the other with metadiscourse removed ones. The results of data analysis showed that students in all three levels of reading proficiency performed better on metadiscourse enriched test booklet than their counterpart groups who took the metadiscourse removed text booklet. In comparing students’ performance on metadiscourse removed text types, it was revealed that they did more poorly on academic metadiscourse removed test booklet than on general one. The findings of this study suggest that making students aware of metadiscoursal features of different text types enhances students’ reading comprehension.